The Effect of Auditor Independence, Competence, Moral Reasoning, and Professionalism on Audit Quality at a Public Accounting Firm (KAP) in Medan City - Arie Pratania Putri; Juanda Chainur; Go Moi; Ester Ovelia Br Siahaan Ester Ovelia Br Siahaan (Institute of Computer Science (IOCS), 2021)
This research aims to find out the impact of independence, competence, moral reasoning, and professionalism of auditors on audit excellence at the Public Accounting Firm (KAP) in the city of Medan. The questionnaire is a technique used in data collection in this study. The technique used was purposive sampling in sampling and the samples obtained were 76 respondents. The analysis tip is to use SPSS software to perform multiple linear analysis. Several tests show that the independence, competence, moral reasoning, and professionalism of auditors have a positive and significant impact on audit excellence. The simultaneous test results indicate that the independent variables of independence, competence, moral reasoning, and professionalism have an impact on the dependent variable on audit excellence.